Repeat cesarean section in subsequent gestation of women from a birth cohort in Brazil - Keila Cristina Mascarello; Alicia Matijasevich; Aluísio J D Barros; Iná S Santos; Eliana Zandonade; Mariângela Freitas Silveira (BMC, 2017)
Abstract Background The current literature indicates increasing concern regarding the number of safe cesarean sections which a woman can undergo, mainly in face of the high cesarean section rates, which are growing in Brazil and worldwide. Aimed to describe the prevalence and associated factors of repeat cesarean section in a cohort of Brazilian women who had a cesarean section in the first birth. Methods This is a prospective cohort study using data from the 2004 Pelotas Birth Cohort. The sample included 480 women who had their first delivery in 2004, regardless of the form of delivery, and who had a second delivery identified in the cohort's follow-ups (in 2005, 2006, 2008, and 2010). Descriptive, bivariate and multivariate analyses using Poisson regression with robust error variance were carried out. Results Among the women who underwent a cesarean section in their first delivery (49.47%), 87.44% had a second surgical delivery. The risk factors for repeat cesarean section included ages 21-34 (PR 1.67, CI 95% 1.07-2.60), not being seen by SUS (Public Healthcare System) in 2004 (PR 2.27, CI 95% 1.44-3.60), and the number of prenatal medical visits, i.e., women with ten or more visits were at 2.33 times higher risk (CI 95% 1.10-4.96) compared to those who had five or fewer visits. Conclusions The proportion of cesarean sections both in the first and in the subsequent delivery is quite high. This high rate may compromise the reproductive future of the women who undergo consecutive cesarean sections with possible consequent complications and changes in care policies for pregnant women should be implemented.